Lentiginous eruption in resolving psoriasis plaques during treatment with ixekizumab: a case report and review of the literature - Pablo Santa María; Fernando Valenzuela; Claudia Morales; Raul De la Fuente; Roberto Cullen (PAGEPress Publications, 2017)
We report the case of a 56-year old male with severe plaque psoriasis that was successfully treated with ixekizumab, a new anti interleukin (IL)-17 monoclonal antibody. During the first months of treatment he developed a lentiginous eruption in the sites of rapidly resolving plaques. Biopsy and immunohistochemistry reports showed elements of both lentigo and post-inflammatory hyper pigmentation. These findings, which have been increasingly described in anti-tumor necrosis factor alpha (TNFα) and anti IL-12/IL-23 therapy, may be explained by the down regulating effect of TNFα and IL-17 on pigmentation genes, which is very rapidly suppressed by ixekizumab, resulting in hyper pigmentation, and by the alteration of mesenchymal-epidermal interaction via keratinocyte growth factor during the inflammatory period, which results in the development of histopathological elements of lentigo.